Self-acronyms in election advertising discourse: rhetorical study - Hardiyanto, Fahrudin Eko (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study aims to reveal the rhetorical form of the acronym itself in the political discourse of the Central Java Pilkada. Through this research, we can find out the rhetorical form of the self-acronym used by the regent/mayor candidate pair in the Pilkada political advertisement. To answer research questions and needs, researchers analyzed research data in the form of banners and billboards. The 2015 local elections in Central Java were carried out through observation techniques and referred to the notes in the advertisement discourse fragments which were allegedly statements which were rhetorical forms of self-acronyms. The conclusion in this study is that there is an acronym that functions as a name shortener and functions as a motto. Acronyms belonging to the name shortening (initialization) are the words Asri, Wali, Si Bagus, Mukti, Jati, Nasir Jos, Breadfruit, Ada, Conscience, Suko, Aman To, Mae, Harjo, Hati Mulya, The Winner, and Must. While those that are classified as mottos are Dadi, Charismatic, Super Sumeh, Sweet, Grateful, and Definitely Fragrant. The results of this study can be implied in making a political advertisement that is good, inspiring, educative, and easy to remember.